OPTIMIZATION OF TNI AL BASE LOGISTIC SUPPORT IN ORDER TO INCREASE THE ABILITY AS A BASE CARRIER IN SUPPORTING OPERATIONS UNITS - Bachtiar Efendi; Avando Bastari; Joko Purnomo (Indonesian Naval Technology College STTAL, 2021)
The development situation of the regional strategic environment is still dominated by the South China Sea conflict (SCS) involving several countries in the ASEAN region. This conflict was mainly triggered by China's unilateral claims regarding the nine dash line area ”(Minister of Defense, 2016). The Indonesian Navy has bases spread across various islands in the Republic of Indonesia and is divided into three Indonesian Fleet commands, namely Koarmada I in Jakarta, Koarmada II in Surabaya and Koarmada II in Sorong. Due to the many obstacles and differences in the character and socio-economic conditions of each area used as a base by the Navy, complex problems arise in determining policies in determining logistical support. This study aims to improve inter-island logistical support capabilities in supporting the Indonesian Navy's operational units. To examine the above problems, it is necessary to identify the threat trend using the content analysis method approach with the SWOT analysis method. In this approach, a proper ranking is also carried out in making decisions using the SWOT matrix calculation which can produce the best strategy formulation by giving the weight and rating of internal and external factors to the four quadrants so that it is known that the results are in quadrant III, which supports the turn around strategy with the difference. between the strengths and weaknesses of 0.18 while the opportunities and threats of 0.73. Keywords: Nine dash line, content analysis method with SWOT analysis method